(3GdLOhi GdGbJUGOjI ddeTQhYGJ GdGSJKeGQjI (B((3c(B18) /s - (3GSeGYjd, jSQi NVQs ((3GdbGgQI(B: s (3eWHYI eQcR GdJYdje GdeaJhM(B, s)
(3OhQI GdeTQhY, OQGSI GdLOhi ddaQU GdGSJKeGQjI, GdHjGfGJ GddGReI dGYOGO OQGSI GdLOhi, GSJNOGeGJ heUGOQ GdCehGd, JbOjQ QHNjI GdeTQhY, GdJOabGJ GdfbOjI aj MGdI TQGA GdBdGJ, GdJOabGJ GdfbOjI ddeTQhY GdeJcGed, Jbjje GdeTQhY ef hLgI fXQ GdeSJKeQ, Jbjje GdeTQhY ef hLgI fXQ GdeSJKeQ GdaQO, GdbjeI GdMGdjI ddJOabGJ GdfbOjI, JWHjbGJ GdbjeI GdMGdjI ddJOabGJ GdfbOjI, GdeYOd GdOGNdj ddYGFOs
(3eQGLY U(B.211 (3edGMb U(B.212s
Keywords: (3GdJehjds; (3GdeTQhYGJs